Punishment For Perpetrators of Distribution of Pornography Who Suffer From Exhibitionism (Decision Number 23/Pid.B/2022/PN Wat) - Farah Nizrinia Aulia; Ainul Azizah; Halif (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2024)
Exhibitionism is a deviant sexual fantasy by showing one’s genitals to other people. This behavior certainly violates the norms of decency and norms which causes unrest and disturbs the peace in the community. Therefore, legal norms must be enforced in order to maintain order and peace and provide legal certainty in social life. Talking about criminal acts cannot be separated from discussing the punishment of the perpetrators of the criminal acts themselves. It can be said that criminal impositions must pay attention to the purpose of punishment which is identical to the punishment that applies for violating a legal rule. In Decision Number 23/Pid.B/2022/PN Wat the defendant admitted to making videos/photos of himself that contained pornography. During the investigation process, the defendant was examined by a psychologist with the results of the examination showing that the defendant suffered from exhibitionism. The panel sentenced the defendant to 10 months imprisonment and a fine of Rp. 250,000,000.